Land Tenure Security and Sustainable Development - Holland, Margaret B.; Masuda, Yuta J.; Robinson, Brian E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book presents a nuanced and accessible synthesis of the relationship between land tenure security and sustainable development. Contributing authors have collectively worked for decades on land tenure as connected with conservation and development across all major regions of the globe. The first section of this volume is intended as a standalone primer on land tenure security and its connections with sustainable development. The book then explores key thematic challenges that interact directly with land tenure security, followed by a section on strategies for addressing tenure insecurity. The book concludes with a section on new frontiers in research, policy, and action. An invaluable reference for researchers in the field and for practitioners looking for a comprehensive overview of this important topic. Margaret B. Holland, PhD, Associate Professor, Department of Geography & Environmental Systems, University of Maryland, Baltimore County. Yuta J. Masuda, PhD, Senior Sustainability and Behavioral Scientist, The Nature Conservancy. Brian E. Robinson, PhD, Associate Professor, Department of Geography, McGill University.
Chapter 1. Property Rights, Tenure Form, and Tenure Security -- Chapter 2. A Historical Perspective on Land Tenure Security -- Chapter 3. Who Defines Land Tenure Security? De Jure and De Facto Institutions -- Chapter 4. Indigenous and Customary Land Tenure Security: History, Trends, and Challenges in the Latin American Context -- Chapter 5. Championing Women$1 (Bs Tenure Security -- Chapter 6. People-Land Relationships on the Path to Sustainable Food Security -- Chapter 7. A Complex Relationship: Large-Scale Land Acquisitions and Land Tenure Security -- Chapter 8. Tenure Security in War-Affected Scenarios: Challenges and Opportunities for Sustainability -- Chapter 9. Land Tenure Insecurity and Climate Adaptation: SocioEnvironmental Realities in Colombia and Implications for Integrated Environmental Rights and Participatory Policy -- Chapter 10. Interaction of Conditional Incentives for Ecosystem Conservation with Tenure Security: Multiple Roles for Tenure Interventions -- Chapter 11.Strategies for Securing Tenure: The Promise and Pitfalls of Formalization -- Chapter 12. Securing Communal Tenure Complemented by Collaborative Platforms for Improved Participatory Landscape Management and Sustainable Development: Lessons from Northern Tanzania and the Maasai Mara in Kenya -- Chapter 13. Beyond the Traditional: Voluntary Market-Based Initiatives to Promote Land Tenure Security -- Chapter 14. Methods to Advance Understanding of Tenure Security: Impact Evaluation for Rigorous Evidence on Tenure Interventions -- Chapter 15. Emerging Research Needs and Policy Priorities for Advancing Land Tenure Security and Sustainable Development./.s
Keywords: Environment; Biotechnology; Human ecology -- Study and teaching; Economic development; Environmental Sciences; Biotechnology; Environmental Studies; Development Studies; Development Studies